Healthy ageing education across Europe: a survey of ENPHE members - Alves Lopes, António (2022)
Background and Purpose Healthy ageing is an optimal status that people could achieve when they currently adapt their physical and psychological evolution that allow them to participate socially with a high level of autonomy. The process of becoming older is a personal process that can be very heterogeneous. This heterogeneity generates different approaches depending on the needs, capacities of adaptation and subject possibilities. Therefore, it is important that any kind of intervention should adapt specifically to each patient. Description With the goal to develop and offer updated education in Healthy Ageing, a group of five universities: Ecole d’Assas (France), Blanquerna-Universitat Ramón Lull (Spain), Univerzita Palackého v Olomouci (Czech Republic), Kolegji Heimerer (Kosovo) and Escola de Saúde do Alcoitão (Portugal) decided to set up a joint adventure as encouraged by ENPHE. Our first step is to benchmark and characterise within Europe the tendencies, the offers and models of best practices. Material / Methods An online questionnaire was developed and sent to all the ENPHE members between January and February of 2017. The survey was composed of twenty close and open questions related to the participant identification, course description and identification of institutional projects in healthy ageing Summary of Results From a population of 136 EMPHE member's we receive 39 complete responses (27%) and the main results are: 69% of the respondents offer courses about healthy ageing; 88% Integrated in the bachelor degree ; mainly for Physiotherapists students (92%); and with the most prevalent topics (above 80%) - Assessment and intervention of clients/populations, multidisciplinary issues and Prevention; the main pedagogical approaches used are lectures (88%), clinical training/field work (77%) and casebased learning (74%); being written or oral examination (81%) the main assessment strategies used. Importance It is very important to empower the individual to become autonomous in deciding how to manage their own ageing process in a healthy way. Any curricula should take in account this reality in order to transform the role of health care professionals and provide them competences to support individuals in this process.